The Influence of Independence, Professionalism and Work Motivation on Auditor Performance at the Makassar City Inspectorate - Basmar, Nur Azizah; Sahidah, Sahidah (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This research aims to analyze and determine the effect of independence on auditor performance; to analyze and determine the effect of professionalism on auditor performance; to analyze and determine the effect of work motivation on auditor performance. The research approach used in this research is a quantitative descriptive approach. The population in this study were all Makassar City Inspectorate APIPs who took part in the inspection task, namely 47 auditors. The sampling method used in this research is the saturated sampling method, which is a sample collection technique when all members of the population are used as samples. The data analysis used in this research is multiple linear regression analysis. Independence, Professionalism and Work Motivation in this research were found to have a positive and significant effect on Auditor Performance.